Study of the psychometric properties and population norms of the C-SHARP in a representative French population. Issue 1 (30th September 2020) - Oubrahim, Leïla; Combalbert, Nicolas
Abstract : Purpose: To fill this gap, this paper aims to translate the children's scale of hostility and aggression: reactive/proactive (C-SHARP) into French and then tested its psychometric properties and established the first French standards. Design/methodology/approach: This paper assess the aggressive behavior of 305 children and adolescents with intellectual disability (ID). This paper tested the scale's factor structure (confirmatory factor analysis), internal consistency and inter-rater reliability. Findings: The results support a factor structure similar to the US version. Factor analysis yielded a five-factor solution, namely, verbal aggression (12 items), bullying (12 items), covert aggression (11 items), hostility (9 items) and physical aggression (8 items). The French-speaking version of the C-SHARP shows good reliability (internal consistency) and good inter-rater reliability. The French version demonstrated encouraging evidence of validity. This paper also established French norms that were similar to US norms. This paper concludes that the French-speaking version of the C-SHARP must benefit from additional psychometric analyzes to confirm its adaptation for research and the clinic. Originality/value: There is no tool currently available in France for the evaluation of aggressive behavior in children and adolescents with ID. The C-SHARP (Farmer and Aman, 2009 ) is the only questionnaire that specifically assesses aggression in children and adolescents with ID, its form, frequency and its proactive or reactive qualities. The French version of the C-SHARP could be a useful diagnostic tool to assess aggressive behavior in children and adolescents with ID and to identify and set up appropriate support strategies.